Exploring the hypoglycemic potential of fresh, semangit, and bosok tempe: A comparative metabolite profile - Astawan, Made; Adurrasyid, Zaid; Novita, Rias R.; Damayanti, Aprilia F.; Saraswati, Saraswati; Wresdiyati, Tutik; Saithong, Pramuan; Chitisankul, Wanida T.; Putri, Sastia P. (Narra Sains Indonesia, 2025)
Tempe, a traditional Indonesian fermented soybean product made with Rhizopus spp., is classified based on fermentation duration into fresh (two days), semangit (five days), and bosok (seven days) varieties, fermented at room temperature (28–30°C). Longer fermentation is believed to enhance its antidiabetic properties. The aim of this study was to compare the metabolite profiles and hypoglycemic activities of fresh, semangit, and bosok tempe made from germinated and non-germinated soybeans. Diabetic rat models were used to assess the effects of these tempe types on body weight, blood glucose levels, serum insulin, pancreatic β-cell count, and glycogen content in liver and muscle tissues. Metabolomic profiling was conducted using gas chromatography-mass spectrometry (GC-MS), followed by principal component analysis (PCA) to assess the influence of fermentation stage and germination. Fresh tempe, especially from germinated soybeans, had the highest moisture content. Fermentation duration significantly influenced color, texture, and pH, with bosok tempe showing the most notable changes. Tempe and gliclazide significantly reduced blood glucose in diabetic rats in vivo, with semangit and bosok tempe restoring levels close to normal. However, weight loss was not reversed. Bosok non-germinated tempe induced the highest insulin levels among tempe treatments and improved β-cell count and density to levels comparable with gliclazide. Glycogen stores in the liver and muscle were significantly restored by tempe, with bosok non-germinated tempe showing the greatest effect. GC-MS profiling identified 154 metabolites, of which 63 were annotated. Fermentation and germination shifted the metabolite profile, with bosok non-germinated tempe showing the highest diversity, including amino acids, sugars, and amines. PCA separated samples by fermentation stage, highlighting metabolite accumulation with prolonged fermentation. The findings revealed that bosok tempe from non-germinated soybeans had the highest abundance of bioactive metabolites, including isoflavones, which likely contributed to its superior antioxidant and hypoglycemic potential compared to other tempe types.